The Relationship Between Medication Compliance and Treatment Outcomes in Chronic Obstructive Pulmonary Disease (COPD) Patients at Pirngadi Hospital, Medan - Chairunnisa Rkt; Syilvi Rinda Sari; Sri Wahyuni; Minda Sari Lubis (Media Farmasi: Jurnal Ilmu Farmasi, 2026)
Chronic Obstructive Pulmonary Disease (COPD) remains a major global health burden, ranking among the leading causes of morbidity and mortality. In Indonesia, the increasing prevalence of COPD is closely linked to smoking behavior, air pollution, and low treatment adherence, which collectively diminish patients’ quality of life and treatment success. Despite various pharmacological advancements, non-adherence to prescribed medication regimens continues to impede optimal therapeutic outcomes. This study aims to analyze the relationship between medication adherence and therapeutic outcomes among outpatient COPD patients at Pirngadi Hospital Medan, as well as to identify factors contributing to non-adherence. The research adopts a quantitative correlational design with a cross-sectional approach, involving 70 respondents selected through quota sampling. Primary data were collected using structured questionnaires, including the General Medication Adherence Scale (GMAS) and the St. George’s Respiratory Questionnaire (SGRQ). Data were processed using IBM SPSS Statistics version 25 and analyzed through univariate and bivariate (Chi-square) tests. The results revealed a significant relationship between medication adherence and therapeutic outcomes (p < 0.05). Patients with higher adherence levels demonstrated better treatment responses and higher health-related quality of life scores. The findings also indicate that smoking status, education level, and duration of illness significantly influence adherence behavior. In conclusion, strengthening patient adherence is essential to improving COPD management outcomes. The study contributes to clinical practice by emphasizing the integration of behavioral and educational interventions into pharmacological therapy. Its novelty lies in combining adherence measurement with quality-of-life assessment in an Indonesian hospital context, offering empirical evidence that supports the development of patient-centered, technology-assisted adherence monitoring systems.